Effects of Chronic Social Stress and Maternal Intranasal Oxytocin and Vasopressin on Offspring Interferon-γ and Behavior - Murgatroyd, Christopher A.; Hicks-Nelson, Alexandria; Fink, Alexandria; Beamer, Gillian; Gurel, Kursat; Elnady, Fawzy; Pittet, Florent; Nephew, Benjamin C. (Frontiers in Endocrinology, 2016)
Recent studies support the hypothesis that the adverse effects of early life adversity and transgenerational stress on neural plasticity and behavior are mediated by inflammation. The objective of the present study was to investigate the immune and behavioural programming effects of intranasal (IN) vasopressin (AVP) and oxytocin (OXT) treatment of chronic social stress (CSS) exposed F1 dams on F2 juvenile female offspring. It was hypothesized that maternal AVP and OXT treatment would have preventative effects on social stress induced deficits in offspring anxiety and social behavior, and that these effects would be associated with changes in interferon γ (IFNγ). Control and CSS exposed F1 dams were administered IN saline, AVP, or OXT during lactation and the F2 juvenile female offspring were assessed for basal plasma IFNγ and perseverative, anxiety, and social behavior. CSS F2 female juvenile offspring had elevated IFNγ levels and exhibited increased repetitive/perseverative and anxiety behaviours and deficits in social behavior. These effects were modulated by AVP and OXT in a context and behavior dependent manner, with OXT exhibiting preventative effects on repetitive and anxiety behaviours and AVP possessing preventative effects on social behavior deficits and anxiety. Basal IFNγ levels were elevated in the F2 offspring of OXT treated F1 dams, but IFNγ was not correlated with the behavioural effects. These results support the hypothesis that maternal AVP and OXT treatment have context and behavior specific effects on peripheral IFNγ levels and perseverative, anxiety, and social behaviours in the female offspring of early life social stress exposed dams. Both maternal AVP and OXT are effective at preventing social stress induced increases in self-directed measures of anxiety, and AVP is particularly effective at preventing impairments in overall social contact. Oxytocin is specifically effective at preventing repetitive/perseverative behaviors, yet is ineffective at preventing deficits in overall social behavior.